Islamic Economic and Banking: A Scientrometric Analysis of Publications During 1989- July 2023 - Dasril, Yosza Bin; arinsandy, yosy; Bin Salahuddin, Shahrul Nizam (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
This Scientometric analysis examines the current status of broad research papers on Islamic Economic and Banking, as published in the Scopus database. The analysis primarily centers on providing descriptions pertaining to the characteristics and trends observed within keywords, authors, and journals. A total of 48 research studies were analyzed in this study. The search utilized to ascertain the research dataset was last updated in July 2023. Descriptive statistical methods were employed, and bibliometric analysis was conducted using the R Biblioshiny tool to ascertain the bibliometric map. In recent years, there has been a substantial increase in the quantity of scholarly articles addressing the topic of Islamic Economic and Banking. Several academic journals publish research on this theme, with Humanomics being one of the most prominent. Demiralp S. is widely regarded as an exceptionally productive writer with local impact by H index. The prevalent keywords observed over the timeframe including 2020 to July 2023 are Communism, Christianity, Capitalism, AAOIFI (The Accounting and Auditing Organization for Islamic Financial Institutions), Moral Economics, and Islamic socialism. This study offers a comprehensive analysis of prevailing patterns in subject matter, keywords, scholarly publications, and authors within the realm of Islamic Economic and Banking. Consequently, it furnishes valuable insights for researchers specializing in this area of study. This particular theme shows potential for further development.